Predicting asthma exacerbations employing remotely monitored adherence. Issue 1 (23rd March 2016) - Killane, Isabelle; Sulaiman, Imran; MacHale, Elaine; Breathnach, Aoife; Taylor, Terence E.; Holmes, Martin S.; Reilly, Richard B.; Costello, Richard W.
Abstract : This Letter investigated the efficacy of a decision‐support system, designed for respiratory medicine, at predicting asthma exacerbations in a multi‐site longitudinal randomised control trial. Adherence to inhaler medication was acquired over 3 months from patients with asthma employing a dose counter and a remote monitoring adherence device which recorded participant's inhaler use: n = 184 (23, 656 audio files), 61% women, age (mean ± sd) 49.3 ± 16.4. Data on occurrence of exacerbations was collected at three clinical visits, 1 month apart. The relative risk of an asthma exacerbation for those with good and poor adherence was examined employing a univariate and multivariate modified Poisson regression approach; adjusting for age, gender and body mass index. For all months dose counter adherence was significantly ( p < 0.01) higher than remote monitoring adherence. Overall, those with poor adherence had a 1.38 ± 0.34 and 1.42 ± 0.39 (remotely monitored) and 1.25 ± 0.32 and 1.18 ± 0.31 (dose counter) higher relative risk of an exacerbation in model 1 and model 2, respectively. However, this was not found to be statistically significantly different. Remotely monitored adherence holds important clinical information and future research should focus on refining adherence and exacerbation measures. Decision‐support systems based on remote monitoring may enhance patient–physician communication, possibly reducing preventable adverse events.